Design, Synthesis, and Antitumor Activities Study of Stapled A4K14-Citropin 1.1 Peptides - Wang, Nan; Xie, Gang; Liu, Chao; Cong, Wei; He, Shipeng; Li, Yinghua; Fan, Li; Hu, Hong-Gang (Frontiers in Chemistry, 2020)
A4K14-citropin 1.1 is a structurally optimized derivative derived from amphibians’ skin secreta peptide citropin which exhibits a wide range of biological activities including anti-bacterial, anti-tumor and neuronal nitric oxide synthase (nNOS) inhibition. However, the application of A4K14-citropin 1.1 as a cancer therapeutic is limited owing to its original conformational flexibility and low stability. In this study, we designed and synthesized a series of all-hydrocarbon stapled peptides derivatives of A4K14-citropin 1.1 and tested their chemical and biological characteristics. Among them, A4K14-citropin 1.1-Sp1 and A4K14-citropin 1.1-Sp4 displayed improved helicity levels, greater protease stability and increased anti-tumor activity compared with the original peptide, which establishes them as promising lead compounds for novel cancer therapeutics development. These results disclosed the important impact of all-hydrocarbon crosslinking on the secondary structure, hydrolase stability, and biological activity of A4K14- citropin 1.1.